Pendampingan Guru SD Negeri Kalibening dalam Implementasi Deep Learning (Pembelajaran Mendalam) Berbasis Proyek - Zico Fakhrur Rozi; Wahidin Wahidin; Nopa Nopiyanti; Rama Saputra; Nugroho Aji Waluyo (LP4MK STKIP PGRI Lubuklinggau, 2025)
The mentoring program for teachers at SD Negeri Kalibening aims to improve their understanding and skills in implementing deep learning through project-based learning (PjBL). The limited experience of teachers in designing and carrying out PjBL serves as the basis for the need for structured training. This community service program was conducted in three training sessions involving seminars, workshops, discussions, and simulated practice using a drill-practice approach. This approach enabled teachers to learn PjBL concepts, develop teaching materials, and implement project-based learning gradually and repeatedly. Evaluation through pre-tests and post-tests showed an increase in the average score from 91 to 105, indicating improved teacher understanding and competence after the mentoring program. In addition, teachers were able to develop lesson plans, student worksheets, and authentic assessment instruments that better aligned with the principles of deep learning. The program also encouraged teachers to design learning activities that are relevant to students’ real-life contexts, thus supporting the creation of meaningful learning experiences. Overall, this mentoring program effectively enhanced the readiness of SD Negeri Kalibening teachers to implement PjBL as part of deep learning in the classroom.